Terorisme dan Deradikalisasi:Pengantar Memahami Fundamentalisme Islam dan Strategi Pencegahan Aksi Terorisme - Suryani, Tamat (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2017)
Terrorism is an imminent threat to the people of the world, not especially Indonesia as a state and nation. The experience in dealing with the Bali bombing case in 2002 has given an important lesson for Indonesia, especially for the police. The notable lesson is that it is necessary, not only to have a concern about the investigation process of terrorism cases but also about de-radicalization efforts to deradicalize the perpetrator. Preventive action against terrorist acts is more meaningful, compared to the ability of police to punish terrorists who did bombings and killed dozens or hundreds of people. Thus, the question is who are those who need to be involved in the deradicalization program?